Evaluation of biofilm cultivation models for efficacy testing of disinfectants against Salmonella typhimurium biofilms - Richter, Anja; Konrat, Katharina; Osland, Ane M.; Brook, Emma; Oastler, Claire; Vestby, Lene K.; Gosling, Rebecca J.; Nesse, Live L.; Arvand, Mardjan (Microorganisms, 2023)
Within the European Union, Salmonella is frequently reported in food and feed products. A major route of transmission is upon contact with contaminated surfaces. In nature, bacteria such as Salmonella are often encountered in biofilms, where they are protected against antibiotics and disinfectants. Therefore, the removal and inactivation of biofilms is essential to ensure hygienic conditions. Currently, recommendations for disinfectant usage are based on results of efficacy testing against planktonic bacteria. There are no biofilm-specific standards for the efficacy testing of disinfectants against Salmonella. Here, we assessed three models for disinfectant efficacy testing on Salmonella Typhimurium biofilms. Achievable bacterial counts per biofilm, repeatability, and intra-laboratory reproducibility were analyzed. Biofilms of two Salmonella strains were grown on different surfaces and treated with glutaraldehyde or peracetic acid. Disinfectant efficacy was compared with results for planktonic Salmonella. All methods resulted in highly repeatable cell numbers per biofilm, with one assay showing variations of less than 1 log10 CFU in all experiments for both strains tested. Disinfectant concentrations required to inactivate biofilms were higher compared to planktonic cells. Differences were found between the biofilm methods regarding maximal achievable cell numbers, repeatability, and intra-laboratory reproducibility of results, which may be used to identify the most appropriate method in relation to application context. Developing a standardized protocol for testing disinfectant efficacy on biofilms will help identify conditions that are effective against biofilms.
Gesehen am 19.05.2023